Increased Global Land Carbon Sink Due to Aerosol‐Induced Cooling. Issue 3 (20th March 2019) - Zhang, Yuan; Goll, Daniel; Bastos, Ana; Balkanski, Yves; Boucher, Olivier; Cescatti, Alessandro; Collier, Mark; Gasser, Thomas; Ghattas, Josefine; Li, Laurent; Piao, Shilong; Viovy, Nicolas; et al.
Abstract: Anthropogenic aerosols have contributed to historical climate change through their interactions with radiation and clouds. In turn, climate change due to aerosols has impacted the C cycle. Here we use a set of offline simulations made with the Organising Carbon and Hydrology In Dynamic Ecosystems (ORCHIDEE) land surface model driven by bias‐corrected climate fields from simulations of three Coupled Model Intercomparison Project Phase 5 (CMIP5) Earth system models (ESMs; IPSL‐CM5A‐LR, CSIRO‐Mk3.6.0, and GISS‐E2‐R) to quantify the climate‐related impacts of aerosols on land carbon fluxes during 1860–2005. We found that climate change from anthropogenic aerosols (CCAA) globally cooled the climate, and increased land carbon storage, or cumulative net biome production (NBP), by 11.6–41.8 PgC between 1860 and 2005. The increase in NBP from CCAA mainly occurs in the tropics and northern midlatitudes, primarily due to aerosol‐induced cooling. At high latitudes, cooling caused stronger decrease in gross primary production (GPP) than in total ecosystem respiration (TER), leading to lower NBP. At midlatitudes, cooling‐induced decrease in TER is stronger than that of GPP, resulting in NBP increase. At low latitudes, NBP was also enhanced due to the cooling‐induced GPP increase, but precipitation decline from CCAA may negate the effect of temperature. The three ESMs show large divergence in low‐latitude CCAA precipitation response to aerosols, which results in considerable uncertainties in regional estimations of CCAA effects on carbon fluxes. Our results suggest that better understanding and simulation of how anthropogenic aerosols affect precipitation in ESMs is required for a more accurate attribution of aerosol effects on the terrestrial carbon cycle. Key Points: Offline simulations on the ORCHIDEE model are used to investigate land C fluxes under different aerosol scenarios using CMIP5 climate Anthropogenic aerosols have increased global land NBP by 11.6–41.8 PgC between 1860 and 2005, mainly through their cooling effects Poor understandings in low‐latitude precipitation response to aerosols lead to large uncertainties on aerosol impacts on NBP